Formulation of Mesoporous Silica Nanoparticles for Controlled Release of Antimicrobials for Stone Preventive Conservation - Presentato, Alessandro; Armetta, Francesco; Spinella, Alberto; Chillura Martino, Delia Francesca; Alduina, Rosa; Saladino, Maria Luisa (Frontiers in Chemistry, 2020)
The biotic deterioration of artifacts of archaeological and artistic interest mostly relies on the action of microorganisms capable of thriving under the most disparate environmental conditions. Thus, to attenuate biodeterioration phenomena, biocides can be used by the restorers to prevent or slow down the microbial growth. However, several factors such as biocide half-life, its wash-out because of environmental conditions, and its limited time of action make necessary its application repeatedly, leading to negative economic implications. Sound and successful treatments are represented by controlled release systems (CRSs) based on porous materials. Here, we report on the design and development of a CRS system based on mesoporous silica nanoparticles (MSNs), as a carrier, and loaded with a biocide. MSNs, with a diameter of 55 nm and cylindrical pores of ca. 3–8 nm arranged as parallel arrays concerning the NP diameter, and with 422 m2/g of specific surface area were synthesized by the sol-gel method assisted by oil in water emulsion. Biocide loading and release were carried out in water and monitored by UV-Vis Spectroscopy; in addition, microbiological assay was performed using as control the MCM-41 mesoporous silica loaded with the same biocide. The role of specific supramolecular interaction in regulating the release is discussed. Further, we demonstrated that this innovative formulation was useful in inhibiting the in vitro growth of Kocuria rhizophila, an environmental Gram-positive bacterial strain. Besides, the CRS here prepared reduced the bacterial biomass contaminating a real case study (i.e., stone derived from the Santa Margherita cave located in Sicily, Italy), after several months of treatment thus opening for innovative treatments of deteriorated stone artifacts.